Francis Sidney Low correspondence - Low, Francis Sidney
ALS (1861 April 18; National Hotel, Washington, D.C.) from Low to his son discussing preparations in Washington, D.C., in case of attack by Confederate sympathizers and rumors that the sympathizers had torn up railroad tracks near Baltimore, Maryland.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baltimore (Md.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Transportation; Washington (D.C.) -- History -- Civil War, 1861-1865.